Purification of HPV16 E6/E7 DNA plasmid-based vaccine using a modified monolithic support - Soares, Alexandra Sabrina Antunes (2013)
Human papillomavirus (HPV) is one of the most common sexually transmitted diseases in the world and has been associated with several human cancers, like cervical cancer. Thus, effective vaccination against Human papillomavirus represents an opportunity for the control of this cancer. The development of therapeutic Human papillomavirus vaccines is required to facilitate the control and eliminate on of a preexisting Human papillomavirus infection. In the last years, the expansion of efficient plasmid DNA purification processes has fostered therapeutics applications like gene therapy and DNA vaccination. Recently, the application of chromatographic operations based on affinity interactions between plasmid DNA or impurities with specific amino acids immobilized in stationary phases has demonstrated good results in the supercoiled plasmid DNA purification. Despite of selectivity achieved with these ligands, conventional matrices present limitations such as the low binding capacity and diffusivity for plasmid DNA samples. Owing to bottlenecks associated to conventional matrices, monolithic supports have emerged as interesting alternatives due to the versatility of their structural characteristics. The research work present in this thesis describes a new strategy that combines the selectivity of arginine as affinity ligand with the versatility of the epoxy-based monoliths to efficiently purify the supercoiled HPV-16 E6/E7 plasmid from other plasmid isoforms and Escherichia coli impurities present in clarified lysate. Additionally, breakthrough experiments were designed to compare the dynamic binding capacity of plasmid DNA to the conventional arginine-agarose matrix with the modified monolithic support. The dynamic binding capacity obtained for the arginine-epoxy monolith was significantly higher than the capacity achieved in the arginine conventional support. Quality control tests indicated that the plasmid sample resultant from the purification step presented a purity degree approximately 100% and an homogeneity higher than 97% of supercoiled isoform, with an extremely reduced level of impurities (RNA, proteins, genomic DNA and endotoxins). Overall, given that the plasmid DNA final product meets regulatory specifications, this combined support can be the key to obtain an adequate non-viral vaccine against a Human papillomavirus infection.